The Impacts of Two Gender-Transformative Interventions on Early Adolescent Gender Norms Perceptions: A Difference-In-Difference Analysis - Villalobos-Dintrans, P (Elsevier Inc., 2023)
Purpose: Inequitable gender norms are widespread and can be harmful to the wellbeing of adolescents. This study estimates the effects of two gender-transformative interventions, Semangat Dunia Remaja or Teen Aspirations (SETARA) and Growing Up Great! (GUG!), on gender norms perceptions and attitudes among very young adolescents in poor urban settings in Bandar Lampung, Semarang, Denpasar (Indonesia), and Kinshasa (Democratic Republic of the Congo). Methods: The study draws from the longitudinal Global Early Adolescent Study, using a quasi-experimental design to evaluate the interventions. Data collection took place between 2017 and 2020. Our analytical samples included 2,159 adolescents in Kinshasa and 3,335 in Indonesia. We conducted a difference-in-difference analysis using generalized estimation equations and generalized linear models, after stratification by site and sex. Results: The interventions shifted a range of gender perceptions, although effects varied by program, city, and sex. SETARA shifted gender-normative perceptions related to traits, roles, and relations, while GUG! effects were more concentrated on attitudes toward chore sharing. SETARA was most effective in Semarang and Denpasar, but not in Bandar Lampung. In addition, both interventions were more consistently effective for girls than boys. Discussion: Gender-transformative interventions can effectively promote gender equality in early adolescence, but effects are program-specific and context-specific. Our findings emphasize the importance of defined theories of change and consistent implementation in gender-transformative intervention. © 2022